2019
DOI: 10.1021/acsami.9b13553
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable Hydrogel Electrolyte toward High-Performance and Reliable Quasi-Solid-State Zn–MnO2 Batteries

Abstract: Zinc-ion batteries are promising power sources, but their practical application is impeded by the Zn dendrite growth and side reactions at the electrode/electrolyte interface. Here, we report that such issues can be effectively addressed by a self-healable hydrogel electrolyte. The electrolyte is comprised of carboxyl-modified poly­(vinyl alcohol) cross-linked by COO–Fe bonding in the presence of Zn­(NO3)2 and MnSO4. A quasi-solid-state Zn–MnO2 battery using the electrolyte delivers a specific capacity up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 34 publications
0
38
1
Order By: Relevance
“…The self-healing mechanism of the hydrogel was ascribed to the COO-Fe bonds. [12] Ma et al reported an all-solid-state Zn-ion battery in which poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and poly(ethylene oxide) (PEO) co-polymer provided hydrogen bonds to enhance the flexibility. [13] As seen from these achievements, it is promising to construct a high-performance self-healing flexible Zn-ion battery by using hydrogel electrolyte and all-in-one 3D electrodes, which have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing mechanism of the hydrogel was ascribed to the COO-Fe bonds. [12] Ma et al reported an all-solid-state Zn-ion battery in which poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and poly(ethylene oxide) (PEO) co-polymer provided hydrogen bonds to enhance the flexibility. [13] As seen from these achievements, it is promising to construct a high-performance self-healing flexible Zn-ion battery by using hydrogel electrolyte and all-in-one 3D electrodes, which have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al observed the self-healing process of a cut PVA-based hydrogel electrolyte by optical microscopy. 103 Surprisingly, it showed nearly no scars at the contact interface after 10 min of self-healing (Figure 8A), proving the structural integrity of the self-healed hydrogel. The ion conductivity of self-healing hydrogels can usually be recovered after self-healing (Figure 8B), whereas irreversible damage of mechanical strength tended to occur after a few self-healing cycles (Figure 8B,C 29 ).…”
Section: Hydrogel Electrolytes With Particular Functionsmentioning
confidence: 80%
“…Here their effects on Zn deposition are discussed. In Zn(NO 3 ) 2 ‐MnSO 4 ‐poly(vinyl alcohol) cross‐linked by COO‐Fe, a porous surface of the cycled Zn can be formed without dendrite, compared with dendrites formed in its aqueous counterpart [34] . The resulted morphology is associated with the regulation between COOH and Zn 2+ at the interface.…”
Section: Electrolyte Regulationmentioning
confidence: 99%